PENDAMPINGAN PEMBUATAN MINUMAN KESEHATAN BERBASIS TANAMAN OBAT INDONESIA BAGI PENYANDANG DISABILITAS DI SLB YAPENAS YOGYAKARTA - Yosi Febrianti; Hady Anshory T; Yulianto .; Novyan Lusiyana (Institut Pendidikan Tapanuli Selatan, 2021)
Persons with disabilities are members of society who are still economically difficult to empower. Based on the results of a need assessment with one of the teachers at SLB YAPENAS, finding the fact that currently in the field of education for persons with disabilities there is no entrepreneurial curriculum available, of course, this is important because persons with disabilities have the potential to be economically independent. The lack of skills and a negative stigma against the abilities of persons with disabilities. This community service program aims to improve and empower the economy and encourage mentally retarded persons to become economically independent business actors. This activity is carried out in several stages, namely facilitating the availability of materials and equipment needed for the production process of health drinks, counseling on Indonesian medicinal plants, providing training in making health drinks from medicinal plants, providing training in making health drinks from medicinal plants and training in product packaging and marketing techniques. This assistance activity resulted in a pilot business for people with disabilities in the form of a health drink based on Indonesian medicinal plants. Business development needs to be done by diversifying commodities to increase and develop the marketing of health drink products.